Crystal structure of isotibolone: a major degradation product of tibolone - Gomez, Ariel; Antonio, Selma Gutierrez [UNESP]; Barros de Araujo, Gabriel Lima; Ferreira, Fabio Furlan; Paiva-Santos, Carlos Oliveira [UNESP] (Royal Soc Chemistry, 2012)
Isotibolone is frequently found as an impurity in tibolone, a drug used for hormone reposition of post-menopause women, due to some inadequate tibolone synthesis or as a result of degradation during drug storage. The presence of isotibolone impurities should be detected and quantified in active pharmaceutical ingredient products of tibolone before its use in the manufacturing of medicaments. The X-ray powder diffraction technique offers the possibility of quantifying isotibolone amounts at different stages of drug production and storage, from the chemical synthesis to the final formulation. In the course of a study involving the quantitative analysis of isotibolone by X-ray powder diffraction, the authors determined the structure of the title compound using a recently developed approach (A. Gomez and S. Kycia, J. Appl. Crystallogr. 2011, 44, 708-713). The structure is monoclinic, space group P2(1) (4), with unit cell parameters a = 6.80704(7) angstrom, b = 20.73858(18) angstrom, c = 6.44900(6) angstrom, beta = 76.4302(5)degrees, V = 884.980(15) angstrom(3) and two molecules per unit cell (Z = 2). The molecules are hydrogen bonded in the ab plane forming layers that are held together in the crystal by van der Waals interactions along the c-axis.